Kajian Saat Pemberian Pupuk Dasar Nitrogen dan Umur Bibit pada Tanaman Brokoli (Brassica oleraceae var. Italica Planck) - Catur Wasonowati (Agrovigor, 2009)
The aim of this research to know the influence of nitrogen base fertilizer timing and right age of seedling after transplanting to growth and harvest of broccoli. The research was done Sumber Brantas Batu. It is a factorial experiment using plot design. There are two factor with three times replications. Factor I (main terrace) is nitrogen base fertilizer timing consist of N0, N1 and N2 where nitrogen  fertilizer given at 0, 7th and  14th day after plant. Factor II  is broccoli seed age consist of  B1, B2, B3 and B4 where seed age are 3, 4, 5 and 6 week. The result of this experiment shows that nitrogen base fertilizer timing and right age of seed can increase growth and harvest of broccoli.  Seed age  5 and 6 give plant height, leave quantity and stem diameter higher  than other age observation. Seed age 3 and 4 week give fresh weight of flower plant 414.53 g/plant. Combination treatment nitrogen base fertilizer timing at 7th day after planting and seed age at 5th  week give leave width, leave width index, total dry weight and harvest higher than other observation. Combination treatment nitrogen base fertilizer timing and seed age at 5th  week cause plant quick flowering (52th day) and harvest (72th day). While  combination treatment  nitrogen base fertilizer timing 14th after flowering  and seed age at 4th week give the highest fresh weight flower that is 2855 g/m2.